The university professor who builds up innovative knowledge for a complex, collaborative and dialogical practice - de Lima Ferreira, Jacques; Carpim, Lucymara; Behrens, Marilda Aparecida (Revista Diálogo Educacional, 2013)
The considerations and reflections referred in this article are results of a qualitative approach research, as a study case, done with 15 professors who teach at a college in the city of Curitiba where majors for technologists are developed, and it also aimed at identifying the teaching methodology adopted by the educators in their pedagogical practice, and if there is any investment on their continuous education, having in mind the educational obstacles educators have been facing in this new century. In the discussions, the investigating process took into account the challenges demanded by the adoption of an innovative, dialogical and cooperative educational attitude which, in a participative and critical manner, needs the adoption of strategies that stimulate the creativity, construction and reconstruction of meaningful knowledge. In that innovative context, the educator must consider the social, political and economic practice. Thus, the educator must adopt a new complexity paradigm (MORIN, 2000, 2001, 2009), in which the educational and methodological process require a proactive attitude in the sense of investing in his/her continuous professional development, especially when it comes to pedagogical practice, using technological resources in the benefit of a collaborative and mediating educational action.